PROBLEMATIKA PERCERAIAN: KASUS DI PENGADILAN AGAMA KOTA SUMEDANG PADA TAHUN 2017 – 2019 - Karamunir Karamunir; Ahmad Subekti; Dzulfikar Rodafi (Jurnal Hikmatina, 2022)
Based on the Compilation of Islamic Law Article 117 States: Talak is a husband's pledge before a Religious court which is one of the causes of the breakup of marriage. Covering the area that the author will examine the Sumedang City Religious Court, there are still many divorces, which occur. The actions taken by the Sumedang community are based on the factors that caused the divorce. The purpose of this study is to find out the factors causing divorce in the Sumedang City Religious Court in 2017-2019 and to find out the impact of legal divorce that occurs.This study uses a qualitative research approach with a field study (case study) The data collection technique used is observation by interview and the main tool is the researcher himself. assist. Data is analyzed by data reduction, data presentation and drawing conclusions. The results show that: (1) the factors causing the divorce in the Sumedang City Religious Court, namely: in accordance with the Compilation of Islamic rules article 116 letters a to h, namely, gambling, drunkenness, leaving one party's error, being executed in prison, more than one wife, constant disputes, domestic violence and the economy.The effects of legal divorce that occurred, namely: (a) the consequences of talak, Giving a proper mut'ah to his former wife and dowry.;. (b) as a result of divorce, an adult child is entitled to choose to obtain financing from his father or mother at the age of 21. (c) the result of khulu', redeeming oneself from the husband. (d) the result of li'an being unable to reconcile and the father's nasab is lost.Keywords: Problematika, Divorce, Sumedang City Religious Court